2011
DOI: 10.1039/c1cc11451d
|View full text |Cite
|
Sign up to set email alerts
|

4-Nitrophenyl sulfenyl chloride as a new precursor for the formation of aromatic SAMs on gold surfaces

Abstract: 4-Nitrophenyl sulfenyl chloride was used as a new precursor for the formation of densely packed aromatic SAMs on gold. The adsorption involves the reductive dissociation of the S-Cl bond. A well-ordered row structure corresponding to a √3 × 4 phase with a molecular area of 27.8 Å(2) is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 41 publications
2
29
2
2
Order By: Relevance
“…3a revealed a phase composed by eight atoms. This phase resemble the well-known octomer observed in sulfur deposition on Au(111) [23][24][25][26]28] (Fig. 3b).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…3a revealed a phase composed by eight atoms. This phase resemble the well-known octomer observed in sulfur deposition on Au(111) [23][24][25][26]28] (Fig. 3b).…”
Section: Resultsmentioning
confidence: 53%
“…The quality of the obtained SAMs depends on the precursors and the experimental conditions like temperature, solvent polarity and pH [1,21,22]. Thus, the adsorption of sulfur containing molecules on gold surfaces may yield SAMs [23]. However, under some conditions, sulfur atoms cleave their bonds with the rest of the molecule and only sulfur is adsorbed.…”
Section: Introductionmentioning
confidence: 98%
“…We have recently shown that these electrochemical characteristics made the arene sulfenyl chlorides excellent new precursors for the formation of aromatic self-assembled monolayers (SAMs) on gold surfaces, which are more difficult to obtain than the aliphatic ones. 84 This means that sulfonyl chlorides may also be good precursors for the formation of SAMs on metal surfaces. A difference though resides in the reduction potentials in the two series; the sulfonyl chlorides being about 1 V more difficult to reduce than the sulfenyl chlorides.…”
Section: Electrolysesmentioning
confidence: 99%
“…[1][2][3] Such properties are controlled simply through appropriate selection of absorbate chemical structure, such as the headgroup and/or terminal functional group. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This advantageous trait enables SAMs to be utilized in a wide array of applications, such as surface wetting, biosensors, nanolithography, and electronic devices. [1][2][3][4] SAMs derived from organic thiols or disulfides on Au(111) have been extensively studied due to their high structural order and chemical stability resulting from strong chemical interactions between the sulfur headgroup and the gold surface.…”
mentioning
confidence: 99%
“…To this end, numerous studies have been performed to probe the formation, structure, and physical properties of SAMs on gold that are prepared by other sulfur (S)-containing precursors, such as protected thiols, 5,9 thiosulfates, 10 thiocyanates, [11][12][13][14] dithiocabamates, 15,16 and sulfenyl chloride. 17,18 Recently, SAMs on Au(111) prepared by organic selenols, protected selenols, and diselenides that have a selenium (Se) headgroup have drawn much attention because of their unique structural features and physical properties. [25][26][27][28][29][30][31][32][33][34] A scanning tunneling microscopy (STM) study showed that the structural quality of aromatic selenolate SAMs is superior to their thiol analogues.…”
mentioning
confidence: 99%